EVALUASI KEPATUHAN AKSESIBILITAS WEB BERDASARKAN WEB CONTENT ACCESSIBILITY GUIDELINES (WCAG) 2.2 LEVEL AA: ANALISIS METODOLOGI GABUNGAN PADA SITUS WEB E-GOVERNMENT BPKP PUSAT - Lupita Chyntia Rachmawati; Verdi Yasin; Anton Zulkarnain Sianipar (Smart Education, 2026)
Abstract: Web accessibility is a crucial aspect in fulfilling the right to information for all levels of society, including people with disabilities. The Financial and Development Supervisory Agency (BPKP) website, as a national strategic information portal, is responsible for providing inclusive digital services. This study aims to evaluate the level of accessibility compliance of the BPKP website based on the Web Content Accessibility Guidelines (WCAG) 2.2 Level AA standard. The research methodology adopts the WCAG-EM 1.0 framework integrated with the Accessibility Compliance Score (ACCS) model. Testing was conducted in a hybrid manner through automated audits using Axe DevTools and Google Lighthouse, as well as manual verification against the latest WCAG 2.2 criteria, namely Focus Not Obscured and Target Size. The evaluation was applied to five main pages of the BPKP website. The results showed that the BPKP website obtained an ACS score of 87.14% with a predicate of